Online teaching style: insights of faculty and students’ perspectives and student engagement - Padmaja Goteti, Venkata; Malay, Jhancy; Sultana, Juveria; Rangraze, Imran Rashid; Harshita, Chilakalapalli Ramya (International Journal of Evaluation and Research in Education (IJERE), 2025)
Medical education had a paradigm shift to online learning during COVID 19 pandemic. The studies conducted identify the benefits and limitations of online learning but not much studies on the faculty and students’ perceptions of faculty online teaching style and the degree of online student engagement. The study was done at Kakatiya Medical College, India. At the end of one year of online teaching to the novice foundation year students during lockdown period, the faculty and students’ perceptions on faculty’s online teaching styles and degree of student engagement were recorded using teaching style inventory (TSI) and online student engagement questionnaire. The study found that 60% of the faculty and 42% of the students perceived that the faculty adopted collaborative teaching style, thus the perception difference was significant (p=0.05). The perception of other teaching styles such as suggestive, assertive, and facilitative among faculty and students were different but statistically not significant. Students positively engaged when faculty practiced facilitative and collaborative teaching styles. To conclude, facilitative, and collaborative, teaching methods help medical students’ motivation for online engagement. Medical students were better engaged with online instruction when instructors gave prompt responses to questions, insightful criticism of work, and individualized coaching.